Digital pedagogy - Liliia V. Volkova; Larisa R. Lizunova; Iuliia A. Komarova (Revista on line de Política e Gestão Educacional)
The article is dedicated to possible changes in the modern paradigm of education that presupposes a traditional model of activity in solving pedagogical problems. The main focus of the article is on two areas of scientific research: the disclosure of the deep meanings of “digital pedagogy” and the formulation of its main problems. The article presents the results of the study of psychological and pedagogical literature, which explains the interpretation of the new concept of “digital pedagogy” by modern Russian researchers. The article also analyzes the scientific literature explaining the problems of digital pedagogy identified on a variety of grounds, including the issues of insufficient quantity or poor quality of learning indicators, the need for the development of a teacher's digital culture, difficulties in the implementation of digital learning into the higher education system etc. The authors investigate the problems of digital pedagogy to define the essence of the concept and formulate its principles.